Modelling of food loss within life cycle assessment: From current practice towards a systematisation. (1st January 2017) - Corrado, Sara; Ardente, Fulvio; Sala, Serenella; Saouter, Erwan
Abstract: Food loss is a major concern from both environmental and social point of view. Life Cycle Assessment (LCA) has been largely applied to quantify the environmental impact of food and to identify pros and cons of different options for optimisation of food systems management, including the recovery of potential waste occurring along the supply chain. However, within LCA case studies, there is still a general lack of proper accounting of food losses. A discrepancy both in food loss definition and in the approaches adopted to model the environmental burden of food loss has been observed. These aspects can lead to misleading and, sometimes, contrasting results, limiting the reliability of LCA as a decision support tool for assessing food production systems. This article aims, firstly, at providing a preliminary analysis on how the modelling of food loss has been conducted so far in LCA studies. Secondly, it suggests a definition for food loss to be adopted. Finally, the article investigates the consequence of using such definition and it proposes potential paths for the development of a common methodological framework to increase the robustness and comparability of the LCA studies. It discusses the strengths and weaknesses of the different approaches adopted to account for food loss along the food supply chain: primary production, transport and storage, food processing, distribution, consumption and end of life. It is also proposed to account separately between avoidable, possibly avoidable and unavoidable food loss by means of specific indicators. Finally, some recommendations for LCA practitioners are provided on how to deal with food loss in LCA studies focused on food products. The most relevant recommendations concern: i) the systematic accounting of food loss generated along the food supply chain; ii) the modelling of waste treatments according to the specific characteristics of food; iii) the sensitivity analysis on the modelling approaches adopted to model multi-functionality; and iv) the need of transparency in describing the modelling of food loss generation and management.